Using the Swansoft Application to Improve Students’ Learning Outcomes in NC/CNC and CAM Machining Engineering - Jamaluddin, Dzikrullah (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2024)
Learning outcomes are a set of competencies obtained by students after participating in learning activities. Most of the current student learning outcomes are still low in setting up and editing CNC programs. Therefore, teachers need to innovate by using applications that are relevant and support improving student learning outcomes. The aim of this research is to use the Swansoft application to improve the learning outcomes of NC/CNC and CAM Machining Engineering students in Class XI of SMK Negeri 2 Sampang. This research is classroom action research which consists of 2 learning cycles for setting up and editing CNC programs using the Swansoft application. The subjects of this research were 33 TPM XI-1 Class students. Based on the results of the test questions given to students, student learning outcomes in cycle I were 87.88% or twenty-nine students had met the KKM. There was an increase in student learning outcomes in cycle II where as many as 100% or 33 students had met the KKM, namely 70. Thus, it can be concluded that the use of the Swansoft application can improve the learning outcomes of NC/CNC and CAM Machining Engineering students in Class XI of SMK Negeri 2 Sampang.